A low-voltage, wide dynamic range CMOS floating active inductor - Sae-Ngow, S.; Thanachayanont, A. (My University, 2003)
This paper presents a novel low-voltage wide dynamic range high frequency floating active inductor in a 0.35-μm CMOS technology. The proposed circuit exhibits 52-dB spurious-free dynamic range while dissipation 2 mW from a single 1.5 V power supply voltage. Using the proposed inductor, a 4th-order bandpass filter was designed at 2-GHz center frequency and achieve Q of 25 with input-referred IP3 of -14 dBV.
Keywords: Active; Analogue circuits